Luminescent covalent organic framework as a recyclable turn-off fluorescent sensor for cations and anions in aqueous solution. Issue 38 (18th September 2019) - Li, Ming; Cui, Zhonghua; Pang, Shirui; Meng, Lingkun; Ma, Dingxuan; Li, Yi; Shi, Zhan; Feng, Shouhua
Abstract : Covalent organic frameworks (COFs) have shown great potential for use in ion sensing; however, applications of existing COFs are limited to sensing either cations or anions. Abstract : Covalent organic frameworks (COFs) have shown great potential for use in ion sensing; however, applications of existing COFs are limited to sensing either cations or anions. In this study, a three-dimensional COF, COF-TT, is constructed by reacting the bis(tetraoxacalix[2]arene[2]triazine) core with tetra( p -aminophenyl)methane to provide a luminescent sensor. COF-TT exhibits ultrahigh thermal stability and exceptional chemical stability in aqueous solutions over a broad pH range from 2 to 14, which signifies immense practical potential for sensing applications. Excellent selectivity and high sensitivity of COF-TT toward Fe 3+ cations and CrO4 2−, Cr2 O7 2−, and MnO4 − anions are evident via luminescence quenching. COF-TT also exhibits excellent recyclability in terms of washing and re-exposure cycles. Both experimental data and theoretical calculations are employed to unveil the mechanisms of the quenching effect and sensing properties of COF-TT.